The imaginal and nymphal morphology of Gilliesia pulchra Zhou, 2004 and its contribution to understanding generic phylogeny (Ephemeroptera: Leptophlebiidae) - Gong, De-Wen; Zhou, Chang-Fa (Zootaxa, 2023)
The nymphs of the leptophlebiid mayfly Gilliesia pulchra Zhou, 2004 have not been reported before, which inhibits deeper understanding of the taxonomy and phylogenetic position of this species and its genus. In 2022, we reared nymphs from southwestern China to the adult stage. All stages are described and photographed here. Nymphs of this species have single deeply-forked gills, somewhat elongated maxillary palpi and two setal tufts on the lingua. Its imaginal characteristics, including wings and penes, are quite similar to G. hindustanica (Gillies, 1951), the type species of the genus. Comparatively, the third species of the genus, G. ratchaburiensis Boonsoong & Sartori, 2015, seems less similar, both in adults and nymphs. Generally, features of G. pulchra nymphs link the two genera Gilliesia Peters & Edmunds, 1970 and Habrophlebiodes Ulmer, 1919 together, while features of the nymphs of G. ratchaburiensis bridge the genera Gilliesia and Dipterophlebiodes Demoulin, 1954.